Determination of cyanide and nitrate concentrations in drinking, irrigation, and wastewaters - Seyed Reza Mousavi; Mahdi Balali-Mood; Bamdad Riahi-Zanjani; Mahmood Sadeghi (Journal of Research in Medical Sciences, 2013)
Background: The chemical contamination of water is a major concern for the environmental and health authorities globally. Some anions present in the water are required for human health, but some of them are harmful. Free cyanide and nitrate are amongst the toxic agents in the aquatic environment. Cyanide is highly toxic for human beings. Industrial plants could be attributed to a major source of these toxic agents. Therefore, cyanide and nitrate concentrations in the drinking and irrigation water wells in the high industrial plants were evaluated. Materials and Methods: The samples (57) were taken from drinking and irrigation water wells as well as from a wastewater refinery in north of Mashhad in three stages - March 2009, June 2010, and July 2010. Determination of cyanide and nitrate were performed by a spectrophotometer using commercially available kits according to the manufacturer′s protocols. Results: Cyanide and nitrate concentrations in the drinking water samples of the three stages were 0.0050 ± 0.0007, 0.0070 ± 0.0018, 0.0008 ± 0.0014 mg/L and 6.50 ± 2.80, 7.20 ± 1.80, 7.50 ± 1.90 mg/L, respectively. Cyanide mean concentration during March, June, and July was significant (P = 0.001), whereas nitrate mean concentration was not (P = 0.5). Cyanide and nitrate concentrations in the irrigation water samples of the three stages were 0.0140 ± 0.0130, 0.0077 ± 0.0025, 0.0087 ± 0.0047 mg/L and 12.37 ± 8.12, 8.04 ± 3.99, 8.40 ± 2.60 mg/L, respectively. Cyanide (P = 0.754) and nitrate (P = 0.705) concentrations were not significant during three occasions. Cyanide and nitrate concentrations in the wastewaters of the three stages were 0.1020 ± 0.033, 0.1180 ± 0.033, 0.1200 ± 0.035 mg/L and 1633.80 ± 40.74, 279.00 ± 152.17, 298.40 ± 304.74 mg/L, respectively. Cyanide (P = 0.731) and nitrate (P = 0.187) concentration in wastewaters were not significant during different months. Conclusion: Although nitrate and cyanide concentrations in the drinking and irrigation water were within the standard range (0.07 mg/L for cyanide and 50 mg/L for nitrate) and was not a health problem at the time of our study, regular estimation of the toxic chemicals due to the development of industrial plants in this area is recommended.